Penerapan Metode Bernyanyi dalam Meningkatkan Penguasaan Mufradat Bahasa Arab - Nurmalia Hidayah; Munirul Abidin (IAI Muhammadiyah Sinjai, 2023)
An important aspect that must be mastered when using language as a means of communication is vocabulary. The vocabulary in Arabic is called mufradat. As a foreign language for Indonesian students, many varied methods are needed to influence students' interest in learning. So that students will feel happy and will not feel bored in learning Arabic mufradat. This research is quasi-experimental. Research data was collected based on the academic results of even and odd semesters. Researchers use pre-test and post-test instruments in every aspect of mufradat assessment. The results of this study concluded that the application of singing methods is effective in mastering Arabic mufradat. Before applying the singing method in odd semesters, the average student test results showed 48.00, while after applying the singing method in even semesters, they reached 89.57. In addition, the N-gain score is included in the high category, which is 0.8138, or 81.38%. This study only focused on improving student learning outcomes based on memorization, pronunciation, and fluency. Then subsequent research can examine other aspects of learning outcomes.